Bevacizumab with 5-fluorouracil, leucovorin, and oxaliplatin versus bevacizumab with capecitabine and oxaliplatin for metastatic colorectal carcinoma: results of a large registry-based cohort analysis - Buchler, Tomas; Pavlik, Tomas; Melichar, Bohuslav; Bortlicek, Zbynek; Usiakova, Zuzana; Dusek, Ladislav; Kiss, Igor; Kohoutek, Milan; Benesova, Vera; Vyzula, Rostislav; Abrahamova, Jitka; Obermannova, Radka (BMC cancer, 2014)
BACKGROUND: Data from the Czech national registry were analysed retrospectively to describe treatment outcomes for capecitabine and oxaliplatin (XELOX) regimen with bevacizumab versus 5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX) regimen with bevacizumab in the first-line therapy for metastatic colorectal cancer (mCRC). METHODS: A national registry containing anonymised individual data on patients treated with targeted therapies was used as a data source. In total, 2,191 mCRC patients who received a first-line therapy with bevacizumab combined with either FOLFOX regimen (n = 1,218, 55.6%) or XELOX regimen (n = 973, 44.4%) were included in the present analysis. RESULTS: No statistically significant difference in survival was observed between the two groups, with median overall survival (OS) of 27.0 months (95% confidence interval [CI] 24.6-29.5 months) and 30.6 months (95% CI 27.8-33.4 months) for FOLFOX/bevacizumab and XELOX/bevacizumab, respectively (p = 0.281). Median progression-free survival (PFS) was 11.4 months (95% CI 10.7-12.1 months) for FOLFOX/bevacizumab and 11.5 months (95% CI 10.8-12.3 months) for XELOX/bevacizumab (p = 0.337). The number of metastatic sites was identified as the most significant predictor of PFS and, together with the presence/absence of metastatic disease at diagnosis, also for OS. CONCLUSIONS: According to this large registry-based analysis, XELOX and FOLFOX regimens have similar effectiveness for use in combination with bevacizumab in the first-line treatment of mCRC. Multiple metastatic sites and the presence of metastatic disease at diagnosis were the strongest negative predictors of OS regardless of backbone chemotherapy regimen.
Keywords: Registries; deoxycytidin; proporcionální rizikové modely; Capecitabine; Humans; fluoruracil; lidé středního věku; Proportional Hazards Models; capecitabinum; Disease Progression; registrace; Leucovorin; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; výsledek terapie; senioři; lidé; humanizované monoklonální protilátky; leukovorin; přežití bez známek nemoci; oxaliplatin; Oxaloacetates; časové faktory; Adult; Antibodies, Monoclonal, Humanized; bevacizumab; Kaplanův-Meierův odhad; kolorektální nádory; Male; Middle Aged; Deoxycytidine; Retrospective Studies; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Czech Republic; Fluorouracil; Bevacizumab; oxalacetáty; Disease-Free Survival; progrese nemoci; organoplatinové sloučeniny; retrospektivní studie; Kaplan-Meier Estimate; Česká republika; mužské pohlaví; Time Factors; Organoplatinum Compounds; Colorectal Neoplasms; Oxaliplatin